Influence of flower and flowering characteristics on seed yield in diploid and tetraploid red clover. Issue 1 (14th November 2014) - Vleugels, Tim; Roldán‐Ruiz, Isabel; Cnops, Gerda; Staub, J.
Abstract Tetraploid red clover (Trifolium pratense L.) often produces insufficient seed to be economically interesting. Numerous studies have identified poor pollination due to long corolla tubes as its cause, but other studies disagree. Therefore, we investigated seed yield, corolla tube length and flowering traits in 244 plants from five diploid and five tetraploid cultivars during 2 years. Tetraploids produced fewer seeds, fewer flower heads and fewer seeds per head, but an equal number of flowers per head when compared to diploids. Although corolla tubes were longer in tetraploid than in diploid red clover (P < 0.001), no correlation between corolla tube length and seed yield was detected. Therefore, the corolla tube length is likely neither the main nor only cause of low seed yield in tetraploid red clover. Instead, three putative causes for low seed yield were identified: tetraploids produced less inflorescences per plant, possessed a lower degree of determinacy and had markedly less seeds per head when compared to diploids. Possible causes for such differences include lower pollen viability and higher rates of embryo abortion.